STUDY OF SEA MINING PIT OPTIMIZATION ON SEA TIN ORE MINING PT. XYZ - Fernanda, Rico
Tin is a metallic mineral that is widely used as a soldering agent, corrosion resistant coating for metals, metal alloys, and other uses. Mining Business Permit Area PT. XYZ has a placer deposit so that underwater mining will be carried out using the Cutter Suction Dreger as a mining tool. To maximize resource utilization, it is necessary to determine optimal mining. Pit optimization is one of the methods to produce Pit Shell which can be used as a reference in making the ultimate pit limit. PT. XYZ plans to conduct pit optimization with the aim of seeing the effect of changes in the selling price of tin and mining costs on the amount of reserves from the ultimate pit limit. Pit optimization in this study uses micromine software that uses the Lerch-Grossman Algorithm in the pit optimization process. Variations in the selling price of tin and mining costs are carried out from -25% to 25% with 5% variation intervals to produce 21 Pit Shells. The increase in price causes the amount of mined reserves to increase while the increase in costs causes the amount of mined reserves to decrease. Changes in tin prices affect changes in the amount of reserves mined more than changes in mining costs.